2004
DOI: 10.1002/pola.20530
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of poly(2‐vinyl pyridine)‐b‐poly(n‐hexyl isocyanate) amphiphilic coil‐rod block copolymer by anionic polymerization

Abstract: A well-defined amphiphilic coil-rod block copolymer, poly(2-vinyl pyridine)b-poly(n-hexyl isocyanate) (P2VP-b-PHIC), was synthesized with quantitative yields by anionic polymerization. A low reactive one-directional initiator, potassium diphenyl methane (DPM-K), was very effective in polymerizing 2-vinyl pyridine (2VP) without side reactions, leading to perfect control over molecular weight and molecular weight distribution over a broad range of initiator and monomer concentration. Copolymerization of 2VP with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 90 publications
0
57
0
Order By: Relevance
“…The colorless solution was maintained at −98°C for 0.5 h. After terminating the polymerization, it was verified by SEC that no block copolymerization occurred. 20,21,38,42 Accordingly, it appears that an undesirable side reaction took place when B was added to the living poly(A) solution. As shown in Fig.…”
Section: Block Copolymerizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The colorless solution was maintained at −98°C for 0.5 h. After terminating the polymerization, it was verified by SEC that no block copolymerization occurred. 20,21,38,42 Accordingly, it appears that an undesirable side reaction took place when B was added to the living poly(A) solution. As shown in Fig.…”
Section: Block Copolymerizationmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] Although polyisocyanates can be prepared readily by anionic polymerization, [12][13][14][15] it has been difficult to synthesize well-defined polyisocyanates via living anionic polymerization because of backbiting reactions resulting in the formation of trimers. 20,21 In these cases, the block copolymerization had to be carried out by sequential addition of the vinyl monomer as the first monomer and HIC as the second monomer due to the very low reactivity of living PHIC, which generally cannot initiate polymerization of vinyl monomers. In particular, we found that the anionic polymerization of n-hexyl isocyanate (HIC) can be successfully performed using sodium naphthalenide (Na-Naph) as the initiator with additives such as 15-crown-5 or sodium tetraphenylborate (NaBPh 4 ), preventing the formation of trimers.…”
Section: Introductionmentioning
confidence: 99%
“…A BCP investigated here is a polystyrene‐ block ‐poly(2‐vinylpyridine) (PS‐ b ‐P2VP) with $\overline {M} _{{\rm n}} $ = 72 kg · mol −1 , PDI = 1.06, and f P2VP = 30% synthesized by living anionic polymerization 34. PS‐ b ‐P2VP BCP micelles were formed by solvating in toluene (5 mg · mL −1 ).…”
Section: Experimental Partmentioning
confidence: 97%
“…These factors lead to the formation of a number of distinct morphologies in the bulk state or aggregation in solution, such as zig-zag lamella, 6 monolayer lamella, 7 perforated lamella, 8 hexagonal strip, [9][10][11] and the puck phase. 17 The helical conformation of the polypeptide and polyisocyanate is due to the intramolecular hydrogen bonding, chiral center in the repeat units, and/or short range restriction of rotation. The two most widely employed helical segments are polypeptides prepared by ring-opening polymerization of NCA, 13,14 and polyisocyanates obtained from transition metal catalyzed coordination polymerization 15,16 or from anionic polymerization of isocyanates.…”
Section: Introductionmentioning
confidence: 99%